A MODIFIED ARTIFICIAL POTENTIAL FIELD METHOD FOR RIVERINE OBSTACLES AVOIDANCE (Jurnal Teknologi (Sciences & Engineering), 2016)
This paper presents a modified artificial potential field (APF) based method for an Autonomous Surface Vessel (ASV) obstacles avoidance in a dynamic riverine environment. The APF method is combined with a balance control scheme to achieve river tracking and obstacles avoidance simultaneously. The APF method is further modified modification to comply with marine collision avoidance regulations (COLREGs). The overtaking and head-on scenarios are simulated in MATLAB platform. The simulation results are compared with other APF methods to prove that the proposed method is efficient for the ASV riverine navigation.Â